The impact of training and professional collaboration on the interobserver variation of lung cancer delineations: a multi-institutional study. (1st February 2019) - Mercieca, Susan; Belderbos, José S. A.; van Baardwijk, Angela; Delorme, Stefan; van Herk, Marcel
Abstract: Background: To assess the impact of training and interprofessional collaboration on the interobserver variation in the delineation of the lung gross tumor volume (GTVp) and lymph node (GTVln). Material and methods: Eight target volume delineations courses were organized between 2008 and 2013. Specialists and trainees in radiation oncology were asked to delineate the GTVp and GTVln on four representative CT images of a patient diagnosed with lung cancer individually prior each course (baseline), together as group (interprofessional collaboration) and post-training. The mean delineated volume and local standard deviation (local SD) between the contours for each course group were calculated and compared with the expert delineations. Results: A total 410 delineations were evaluated. The average local SD was lowest for the interprofessional collaboration (GTVp = 0.194 cm, GTVln = 0.371 cm) followed by the post-training (GTVp = 0.244 cm, GTVln = 0.607 cm) and baseline delineations (GTVp = 0.274 cm, GTVln: 0.718 cm). The mean delineated volume was smallest for the interprofessional (GTVp = 4.93 cm 3, GTVln = 4.34 cm 3 ) followed by the post-training (GTVp = 5.68 cm 3, GTVln = 5.47 cm 3 ) and baseline delineations (GTVp = 6.65 cm 3, GTVln = 6.93 cm 3 ). All delineations were larger than the expert for both GTVp and GTVln ( p < .001). Conclusion: Our findings indicate that image interpretational differences can lead to large interobserver variation particularly when delineating the GTVln. Interprofessional collaboration was found to have the greatest impact on reducing interobserver variation in the delineation of the GTVln. This highlights the need to develop a clinical workflow so as to ensure that difficult cases are reviewed routinely by a second radiation oncologist or radiologist so as to minimize the risk of geographical tumor miss and unnecessary irradiation to normal tissue.